PEMAHAMAN SISTEM PENGENDALIAN INTERN, ASIMETRI INFORMASI, KOMPENSASI DAN KENDALI RELIGIUS TERHADAP PENGUNGKAPAN FRAUD AKUNTANSI OLEH AKUNTAN PUBLIK - Abdul Manan; Windasari Rahmawati; Nasron Alfianto (Jurnal Dinamika Sosial Budaya, 2017)
Fraud accounting a phenomenon that has not been detected by a public accountant as a party that checks its financial statements. Latest Fraud in the field of accounting re-occur in the giant company and not tracked by an external accountant (public accountant). The beginning of the first half of 2017 has emerged the issue of accounting fraud in British Telecom. On one of its subsidiaries in Italy. The public accounting firm doing the audit work on British Telecom is not a small public accounting firm but one of the bigfour, Price Waterhouse Coopers (PwC). The British Telecom accounting fraud mode in Italy is actually relatively simple and much discussed in the literature of auditing lectures yet many auditors fail to detect it. To know the existence of accounting fraud the auditor seeks to understand corporate governance and knowledge of forensic accounting is adequate. In this study, forensic accounting variables, internal control system, information asymmetry, compensation and religious control as variables used to detect and understand the presence or absence of accounting fraud in the company audited by the auditor.